SPE Improved Oil Recovery Symposium 2012
DOI: 10.2118/153866-ms
|View full text |Cite
|
Sign up to set email alerts
|

Microbial EOR: A Quantitative Prediction of Recovery Factor

Abstract: Microbial Enhanced Oil Recovery (MEOR) is a promising EOR technique. Feeding bacteria so that they can be stimulated to produce metabolites is a good way to increase recovery factors. In this paper, we present a mathematical model which describes a MEOR process and can be applied to estimate the recovery factor.A one-dimensional isothermal model, comprising displacement of oil by water containing bacteria and nutrients, is studied. The model is composed by a hyperbolic system of four partial differential equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…For the nutrients consumed for bacteria, we consider the yield coefficient Y n , which we included in the R n term. In the absence of IFA, one relation for the production rate of surfactants is given by [23]…”
Section: Transport Equationsmentioning
confidence: 99%
“…For the nutrients consumed for bacteria, we consider the yield coefficient Y n , which we included in the R n term. In the absence of IFA, one relation for the production rate of surfactants is given by [23]…”
Section: Transport Equationsmentioning
confidence: 99%
“…Numerical modeling has been used to attempt the quantitative prediction of the performance of the MEOR process [73]. A study conducted by Eduarda et al [79] in which a finite difference method was applied, indicated that appropriate bacterial growth within the reservoir is the determining variable affecting the oil recovery factor.…”
Section: Chemical Enhanced Oil Recovery (Ceor) -A Practical Overviewmentioning
confidence: 99%
“…For the relative permeability curves for oil k ro and water k rw , the Corey correlations are used [38]: (37) where s w is water saturation, k rowi is the endpoint relative permeability for oil (at s wi ), k rwor is the endpoint relative permeability for water (at 1−s or ), s wi is the initial water saturation, s * or is the residual oil saturation, and the exponents for water and oil are a and b, respectively.…”
Section: Appendix Basis For Sigmoidal Curves For Sporulation and Reacmentioning
confidence: 99%
“…MEOR models have been developed with different selections of mechanisms of bacterial actions [10,14,37,40,51]. However, as mentioned earlier, the main contribution to the additional oil recovery originates from in situ surfactant production and the selective plugging effect.…”
Section: Introductionmentioning
confidence: 99%